Architectural Data Flow Analysis for Detecting Violations of Confidentiality Requirements - Seifermann, Stephan (The Karlsruhe Series on Software Design and Quality, 2022)
Software vendors must consider confidentiality especially while creating software architectures because decisions made here are hard to change later. Our approach represents and analyzes data flows in software architectures. Systems specify data flows and confidentiality requirements specify limitations of data flows. Software architects use detected violations of these limitations to improve the system. We demonstrate how to integrate our approach into existing development processes.